Book Review of "Attachment to Pets: An Integrative View of Human-Animal Relationships with Implications for Therapeutic Practice" - Norris, Robin R. (Canadian Journal of Counselling and Psychotherapy, 2012)
Attachment to Pets presents an interdisciplinary view of the concept of attachment that is crucial to the understanding of human-animal interactions in the therapeutic milieu. The authors incorporate evolutionary biology, ontogeny, psychology, and psychophysiology to engage the reader in a cross-disciplinary journey into the history of attachment and caregiving, the role of the oxytocinergic system, and the dynamics that can be revealed in the interactions between humans and animals in therapy. Overall, Attachment to Pets provides a foundational basis for further research in this area.